The Impediment of Abduction of the 1983 CIC (c. 1089) in the Context of Forced Marriage - Hurtado de Mendoza Domínguez, Carlos (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
The impediment of abduction regulated in the Code of the Latin Church and in the Code of Canons of the Eastern Churches contemplates two of the most radical coercive mechanisms to obtain matrimonial consent, abduction and the retention intuitu matrimonii. The present study analyses canon 1089 of the 1983 CIC with the aim of assessing the convenience and opportunity of maintaining this canonical figure. In order to do so, it is necessary to take into account the phenomenology of forced marriage, in terms of its causes, expressive forms of coercion and consequences, as currently described by international norms. Several questions arise in this reflection. Firstly, whether the configuration of the impediment, only in relation to the abducted woman, constitutes discrimination and whether it responds to normative schemes typical of a restorative legal technique; secondly, how the active subject of the ruling norm should be interpreted, taking into account the social and cultural contexts of forced marriage; and, finally, whether from the victims’ experience there is a «safe and free place» that guarantees a minimum threshold of autonomy for the ordinary cessation of the impediment or whether, on the contrary, the set of coercive forces that operate in the unwanted marriage reinforce the presumption of the defect of consent and suggest attending to the process of formation of the nuptial will, integrating the situations of abduction and retention with a view to marriage in the chapter of vis vel metus.